Skrining Isolat Bakteri Actinomycetes dari Sumber Air Panas Ai’ Sipant Lotup yang berpotensi sebagai Agen Antifungi terhadap Fungi Malassezia sp. (M1). - Novik Nurhidayat, Nurjanah Rahmawati (Jurnal Protobiont, 2019)
Actinomycetes is a filametous gram-positive bacteria. This group of bacteria can produce bioactive compounds, one of which is antifungal compounds. This study aims to determine the antifungal activity of  Actinomycetes isolates from hot springs Ai 'Sipant Lotup in Sanggau Regency, West Kalimantan, to against Malassezia sp. (M1) through antifungal activity test using paper disc diffusion method. Actinomycetes isolates which have antifungal activity against Malassezia sp. (M1) are Microbispora sp. (S311A) and Streptomyces sp. (H2232). Based on the classification of inhibitory zone activity, the  isolates were classified as strong  (S311A) and  medium (H2232)  to against Malassezia sp. (M1).